Safety profile, antiviral capacity, and liver protection of a nasal therapeutic vaccine in patients with chronic hepatitis B: Five-year-follow-up outcomes after the end of treatment - Al Mahtab, Mamun; Akbar, Sheikh Mohammad Fazle; Aguilar, Julio Cesar; Yoshida, Osamu; Khan, Sakirul; Gerardo, Guillen Nieto; Hiasa, Yoichi (Frontiers in Medicine, 2023)
There is a pressing need to develop a new and novel drug for treating patients with chronic hepatitis B (CHB) as commercially available antiviral drugs are endowed with safety and efficacy concerns. A phase III clinical trial was accomplished with a therapeutic vaccine containing two antigens of hepatitis B virus (HBV) (named NASVAC) in 78 patients with CHB expressing both HBV DNA and elevated levels of alanine aminotransferase (ALT)) in the blood. Five years after the end of treatment (EOT) with NASVAC, 60 NASVAC-recipient patients were enrolled in this long-term follow-up study to evaluate the safety, antiviral potentiality, and liver-protecting capacity of NASVAC. NASVAC exhibited an excellent safety profile five years after EOT. The levels of HBV DNA in the sera were reduced in 55 of 60 patients and 45 of them were negative for HBV DNA in the sera. The levels of ALT were also normalized in 40 of 60 patients five years after EOT. None of the patients receiving NASVAC developed liver cirrhosis or liver cancer. The present study is the first to exhibit the long-term follow-up data of a finite immune therapy for CHB that is safe and endowed with potent antiviral and liver-protecting capacities.